Research on Pressure Compensation for the Rubidium Atomic Clock Working in Atmospheric Environment - LI Junyao; LI Chengkang; ZHAO Feng; WANG Chen; WANG Fang; KANG Songbai; WANG Pengfei; MEI Ganghua; MING Gang (Chinese Journal of Magnetic Resonance)
Vapor cell rubidium atomic clock is widely used in the fields of satellite navigation and communication with advantages including small size, light weight, low power and maintenance cost. The high-performance vapor cell rubidium atomic clocks in BDS-3 (Beidou-3 Navigation Satellite System) demonstrate exceptional stability, achieving 5E-13/ τ−−√ within 1~10 000 s and exceeding 3E-15 at one day. However, in atmospheric environment, due to environmental factors, particularly the influence of atmospheric pressure, the long-term stability deteriorates by 1 to 2 orders of magnitude after 1 000 s. This paper proposes a high-precision pressure compensation method by analyzing noise introduced from compensation algorithm and conducting sufficient experimental verification. After compensation, the long-term stability at 10 000 s of ground-type rubidium atomic clock is improved by approximately one order of magnitude, reaching a frequency stability better than 6.5E-15.